Estudo químico de alcaloides nas raízes de Worsleya procera (Lem.) Traub (Amaryllidaceae) - Salarini, Karla Loriatto Gonring (2017)
Comprising more than 1600 species worldwide, the Amaryllidaceae family is distinguished by the production of isoquinolinic alkaloids which are assigned biological activities such as: antitumor, anti-inflammatory, analgesic, antimicrobial and reversible acetylcholinesterase inhibitory action. In Brazil, 141 species of Amaryllidaceae have been described, of which 62 are endemic and some are threatened of extinction, as is the case of Worsleya procera (Lem.) Traub, the only representative of the genus Worsleya. This species occurs exclusively in the State of Rio de Janeiro (RJ) and no published phytochemical studies have been found for this species. In order to carry out the phytochemical study on alkaloids of the species, samples of the roots of Worsleya procera (Lem.) Traub were collected in the Permanent Protection Area of Petrópolis (RJ) and after maceration and acid-base extraction, extracts enriched in alkaloids were obtained. Preliminary analysis by gas chromatography coupled to a mass spectrometer (CG-MS) identified 12 compounds already known, as well as other 18 non-identified by the University of Barcelona database. Using chromatographic, spectroscopic and spectrometric techniques, it was possible to isolate and identify the alkaloids lycorine, tazettine, 3-epimacronine, homolycorine, albomaculine, ismine and trisphaeridine. The roots of Worsleya procera are a rich source of alkaloids, especially of lycorine and tazettine. The identification of these compounds may contribute to chemotaxonomy of this species as well as in research involving biological activities due to the amount of isolated alkaloids.